Pendidikan, kesehatan dan pertumbuhan ekonomi terhadap tingkat kemiskinan dengan zakat sebagai variabel moderasi di Jawa Tengah - Hidayah, Sita Sari Nur; Chang, Iskandar (Journal of Economics Research and Policy Studies, 2024)
This study aims to analyze the impact of education, health, and economic growth on poverty levels in Central Java from 2018 to 2022, with zakat as a moderating variable. A quantitative research approach with panel data was employed, and the data analysis method used was Moderate Regression Analysis (MRA). The findings of this study indicate that, individually, education and health variables have a negative but insignificant relationship with poverty levels. In contrast, the economic growth variable has a significant negative relationship with poverty levels. The moderating variable, zakat, does not moderate the relationship between education and poverty levels; however, it does moderate the relationship between health and economic growth on poverty levels.